2007
DOI: 10.1074/jbc.m611502200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Studies of Uropathogenic Escherichia coli and Host Urothelial Cells when Intracellular Bacterial Communities Are Assembled

Abstract: Uropathogenic Escherichia coli (UPEC), the principal cause of urinary tract infection in women, colonizes the gut as well as the genitourinary tract. Studies of mice inoculated with UTI89, a sequenced isolate, have revealed a complex life cycle that includes formation of intracellular bacterial communities (IBCs) in bladder urothelial cells. To understand how UPEC adapts to life in IBCs, we have used GeneChips and/or quantitative reverse transcriptase PCR to study UTI89 recovered from the distal gut of gnotobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
146
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 58 publications
12
146
0
Order By: Relevance
“…Our approach has uncovered a broad range of host factors not previously known to regulate innate defense to bacterial UTI. Several genes identified in this study are consistent with prior reports that profiled mouse bladder previously and mapped responses in foci of uroepithelium infected with intracellular UPEC pods, which displayed localized responses (50,57). The whole tissue approach we have used gives broader definition to the total bladder transcriptome of UTI.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our approach has uncovered a broad range of host factors not previously known to regulate innate defense to bacterial UTI. Several genes identified in this study are consistent with prior reports that profiled mouse bladder previously and mapped responses in foci of uroepithelium infected with intracellular UPEC pods, which displayed localized responses (50,57). The whole tissue approach we have used gives broader definition to the total bladder transcriptome of UTI.…”
Section: Discussionsupporting
confidence: 77%
“…Notably, many of the responses identified in the whole bladder transcriptome presented in this work are consistent with those observed in localized responses to intracellular bacterial communities in bladder urothelial cells, as previously reported (57). Of particular note were localized urothelial responses to intracellular bacterial communities such as those directed at opposing UPEC salvage of host cell iron and facilitation of glucose import and epithelial structural integrity (57). Many of these responses are consistent with the genes, such as lipocalin 2 (Lcn2) and hexokinase 2 (Hk2), identified as highly upregulated in the whole bladder transcriptome of UPEC cystitis in this study.…”
Section: Discussionsupporting
confidence: 62%
“…32,33 In UPEC, a metabolomic study by Henderson et al demonstrated a prevalence of yersiniabactin in UPEC vs. coincident rectal isolates, indicating a role for this siderophore during pathogenesis. 31 Consistent with this hypothesis, yersiniabactin biosynthesis genes have been shown to be highly expressed in IBCs in a murine model of infection 36 (Hadjifrangiskou et al, unpublished). More recent studies have demonstrated that disruption of salicylate production by the yersiniabactin biosynthesis pathway in UPEC results in dramatic loss of UPEC pellicle biofilm, which is restored upon exogenous addition of micromolar concentrations of salicylate (Henderson and Hung et al, unpublished data).…”
supporting
confidence: 56%
“…Growth in urine induces expression of a variety of iron acquisition systems in UPEC, demonstrating that urine is an iron-limiting environment (47). Additionally, IBC formation correlates with induction of genes involved in acquiring iron from heme and siderophores (48). Because iron and biofilm formation both play a significant role in UPEC pathogenesis, it is tempting to speculate that the iron-induced biofilm formation we describe here may contribute to UPEC virulence.…”
Section: Discussionmentioning
confidence: 88%